Multi-tiered systems of support for school attendance and its problems: An unlearning perspective for areas of high chronic absenteeism - Kearney, Christopher A.; Graczyk, Patricia A. (Frontiers in Education, 2022)
School attendance problems (SAPs) are a vexing challenge for many educational districts given their complexity, heterogeneity, and opacity. One potential coordinated, integrated approach to ameliorate SAPs and boost school attendance is to leverage existing school-based systems already designed to address multiple individual domains of functioning in students. Multi-tiered systems of support frameworks for school attendance and its problems have been developed but remain in the nascent stage. The purpose of this perspective article is to begin a discussion as to how such frameworks for SAPs could be fundamentally reconfigured in areas with very high rates of chronic absenteeism. Recommendations are provided at each tier, with the understanding that original notions of how tiers are ostensibly constructed and aimed must be unlearned in these circumstances.